Whey Protein Isolate-Chitosan PolyElectrolyte Nanoparticles as a Drug Delivery System - Yadollahi, Zahra; Motiei, Marjan; Kazantseva, Natalia; Císař, Jaroslav; Sáha, Petr (Molecules (Basel, Switzerland), 2023)
Whey protein isolate (WPI), employed as a carrier for a wide range of bioactive substances, suffers from a lack of colloidal stability in physiological conditions. Herein, we developed innovative stabilized PolyElectrolyte Nanoparticles (PENs) obtained by two techniques: polyelectrolyte complexation of negatively charged WPI and positively charged chitosan (CS), and ionic gelation in the presence of polyanion tripolyphosphate (TPP). Therefore, the WPI-based core was coated with a CS-based shell and then stabilized by TPP at pH 8. The nanostructures were characterized by physiochemical methods, and their encapsulation efficiency and in vitro release were evaluated. The spherical NPs with an average size of 248.57 ± 5.00 nm and surface charge of +10.80 ± 0.43 mV demonstrated high encapsulation efficiency (92.79 ± 0.69) and sustained release of a positively charged chemotherapeutic agent such as doxorubicin (DOX). Z-average size and size distribution also presented negligible increases in size and aggregates during the three weeks. The results obtained confirm the effectiveness of the simultaneous application of these methods to improve the colloidal stability of PEN.
Keywords: nosiče léků; syrovátkové proteiny; velikost částic; chitosan; Drug Carriers; TPP; Polyelectrolytes; WPI; Chitosan; Drug Delivery Systems; polyelektrolyty; lékové transportní systémy; colloidal stability; Nanoparticles; Particle Size; Whey Proteins; nanočástice